TUTURAN IMPERATIF MAMAH DEDEH PADA ACARA MAMAH DAN AA BERAKSI DI STASIUN TELEVISI INDOSIAR - Ewika Amelia; Hasnah Faizah AR; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study discusses the imamative imperative of Mamah Dedeh on Mamah dan Aa Beraksi on television stations Indosiar. The objectives of study are to describe the form and meaning of imperative speech of Mamah Dedeh on Mamah dan Aa Beraksi on television stations Indosiar. The method used is descriptive method with qualitative approach. There are four techniques used for data collection, i.e. observation techniques, listening techniques, recording techniques, and note-taking techniques. The source of data is the whole speech of Mamah Dedeh on Mamah Dedeh and Aa Beraksi on television stations Indosiar. There are 98 data which consist of 49 imperative form, and 49 data imperative meaning. The result of this study shows that there are five form of imamative imperative that are : imperative orders, solicitation, prohibition, permition, and command. Moreover this study found that there are mine imperative meanings that are : prohibition, command, orders, request, appealing, solicition, expectation, congratulation, and recommandation.Keywords : Imamative imperative, imperative form, imperative meaning